2014
DOI: 10.1371/journal.pone.0097810
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Inhibits Sympathetic Nerve Sprouting and Restores β-Adrenergic Receptor Balance in Rats with Myocardial Infarction

Abstract: BackgroundCardiac sympathetic nerve sprouting and the dysregulation of β-adrenergic receptor (β-AR) play a critical role in the deterioration of cardiac function after myocardial infarction (MI). Growing evidence indicates that exercise provides protection against MI. The aims of this study were to investigate whether aerobic exercise following MI could inhibit sympathetic nerve sprouting and restore the balance of β3-AR/β1-AR.MethodsMale Sprague-Dawley rats were divided into three groups: sham-operated contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Moreover, authors observed increased activation of NO synthase 1 (NOS1) and NOS2 in the heart of animals submitted to PE, indicating possible modulation of β3-AR through NO pathway. Therefore, considered together, these results indicate that the protective effect of PE in MI can be modulated by β3-AR/NO pathway 79 .…”
Section: The Effects and Mechanisms Of Pe On Mi: Evidence From The Sumentioning
confidence: 63%
See 3 more Smart Citations
“…Moreover, authors observed increased activation of NO synthase 1 (NOS1) and NOS2 in the heart of animals submitted to PE, indicating possible modulation of β3-AR through NO pathway. Therefore, considered together, these results indicate that the protective effect of PE in MI can be modulated by β3-AR/NO pathway 79 .…”
Section: The Effects and Mechanisms Of Pe On Mi: Evidence From The Sumentioning
confidence: 63%
“…However, animal studies have shown that if PE starts as soon as possible after MI this can further improve heart function, increasing maximum stroke volume, ejection fraction and attenuating the deterioration of LV contractility. These beneficial effects may be associated with PE-induced proliferation of cardiomyocytes, angiogenesis, attenuation of apoptosis in cardiomyocytes, due to improvement of myofilaments and management of intracellular calcium (Ca 2+ ) 79 .…”
Section: The Effects and Mechanisms Of Pe On Mi: Evidence From The Sumentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these data demonstrate that, although CITED4 expression does not confer acute cardioprotection, it does markedly mitigate adverse remodeling after ischemic injury. Since exercise training has independent beneficial effects on both initial infarct size and late adverse remodeling (38), we infer that CITED4-independent pathways mediate the former, while CITED4-dependent pathways are likely major contributors to the latter. Adverse remodeling is an important cause of human heart failure that may be more amenable to therapeutic targeting than initial infarct size, given the unanticipated nature of acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 97%